The Role of Antioxidant Activity of Chitosan-Pinus merkusii Extract Nanoparticle in against Lead Acetate-Induced Toxicity in Rat Pancreas - G. Wardani; Ernawati; K. Eraiko; S. A. Sudjarwo (Veterinary Medicine International)
Lead is one of the heavy metals with oxidative stress that causes toxicity in human and animals. The aim of this study was to evaluate the antioxidant activity of Chitosan-Pinus merkusii extract nanoparticle on lead acetate-induced toxicity in rat pancreas. Chitosan-Pinus merkusii nanoparticles were identified by Particle Size Analysis (PSA) and Scanning Electron Microscope (SEM). The male rats used were divided into a control group (treated with distilled water), lead acetate group (injected with lead acetate at 20 mg/kg BW i.p), and the treatment group (treated orally with Chitosan-Pinus merkusii nanoparticle at 150 mg; 300 mg; 600 mg/kg BW and injected with lead acetate at 20 mg/kg BW i.p). Blood samples were taken to measure glucose and insulin level. The pancreas tissues were also collected to evaluate the malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GPx), and histological evaluations of cell damage. The PSA showed that the size of Chitosan-Pinus merkusii nanoparticle was 530.2 ± 38.27 nm. The SEM images revealed an irregular shape, and the morphology showed a rough surface. Administration of lead acetate resulted in a significant increase in glucose and MDA levels as well as a decrease in the level of insulin, SOD and GPx when compared with the control group, while that of 600 mg/kg BW of Chitosan-Pinus merkusii nanoparticle gave a polar result. The lead acetate induced loss of pancreatic cells normal structure and necrosis, while Chitosan-Pinus merkusii nanoparticle inhibited it. It could be concluded that Chitosan-Pinus merkusii nanoparticle has a potential to be a powerful agent and may be useful as an antioxidant against free radical-induced oxidative stress and pancreatic cell damage mediated by lead acetate intoxication.